Does PIN measure information? Informed trading effects on returns and liquidity in six emerging markets (2015)
Market microstructure models imply that informed trading reduces liquidity and moves prices in the direction of the information. We test this implication using the dynamic PIN model (Easley, Engle, O'Hara and Wu 2008) as a time-varying measure of informed trading in the six largest Latin America stock markets. Under alternative specifications and robustness tests, the results suggest that signed dynamic PIN is related to returns, as a proxy for information asymmetry rather than just liquidity effects. These results contribute to the ongoing discussion on whether PIN is a valid informed trading measure, and to a better understanding of price formation in emerging markets.